2020
DOI: 10.1371/journal.pone.0229612
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and high-risk subgroups of severe acute maternal morbidity in twin pregnancy: A population-based study

Abstract: Catherine Deneux-Tharaux 1 , for the JUmeaux MODe d'Accouchement (JUMODA) study group and the Groupe de Recherche en Obsté trique et Gyné cologie (GROG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
2
0
2
Order By: Relevance
“…However, these proportions are not directly comparable due to differences in the initial cohorts, in particular the GA at delivery and exclusion of underweight women from their standard population. The initial IOM cohort (37% White, non‐Hispanic; 19% Hispanic; 43% African American; 1% Asian [Luke et al, 2003 ]) was more racially/ethnically diverse the JUMODA standard population included in this analysis and the full JUMODA cohort (country of birth: 82% Europe; 11% North Africa; 6% sub‐Saharan Africa; 2% other [Korb et al, 2020 ]) though composition of the IOM standard population is not reported and could differ from their initial cohort given racial/ethnic disparities in birth outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, these proportions are not directly comparable due to differences in the initial cohorts, in particular the GA at delivery and exclusion of underweight women from their standard population. The initial IOM cohort (37% White, non‐Hispanic; 19% Hispanic; 43% African American; 1% Asian [Luke et al, 2003 ]) was more racially/ethnically diverse the JUMODA standard population included in this analysis and the full JUMODA cohort (country of birth: 82% Europe; 11% North Africa; 6% sub‐Saharan Africa; 2% other [Korb et al, 2020 ]) though composition of the IOM standard population is not reported and could differ from their initial cohort given racial/ethnic disparities in birth outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Tujuan penelitian ini menganalisis faktor yang berhubungan dengan kejadian preeklampsi di Praktik Mandiri Bidan X di Bangkalan. Teknik pengambilan sampel pada penelitian ini yaitu simple random sampling (9) , artinya dengan menetapkan subjek yang memenuhi kriteria penelitian dan mempunyai kesempatan yang sama. Variabel independen pada penelitian ini adalah usia, pendidikan, pekerjaan, kecemasan dan kepatuhan ANC.…”
Section: Pendahuluanunclassified
“…Preeklampsia menyebabkan efek samping langsung pada ibu, termasuk gangguan hepatorenal dan sistem koagulasi (Ackerman et al, 2019). Jika tidak diobati atau dalam bentuk yang parah, edema paru ibu, eklampsia, cedera otak, dan kematian dapat terjadi (Habersaat et al, 2014;Korb et al, 2020;Stevens et al, 2017). Perfusi uteroplasenta yang tidak adekuat menyebabkan pertumbuhan janin restriksi dan/atau solusio plasenta, yang mengakibatkan indikasi kelahiran prematur atau lahir mati.…”
Section: Pendahuluanunclassified